FEATURES OF LYMPHADENECTOMY PERFORMANCE IN PATIENTS WITH STOMACH CANCER IN RADICAL SURGERY IN CASE OF VARIANT STRUCTURE OF CELIAC TRUNK - V. M. Sedov; I. N. Danilov; A. N. Yaitskiy; A. A. Zakharenko; K. N. Vovin; A. L. Bykova (Вестник хирургии имени И.И. Грекова)
The authors developed and described an algorithm and technical aspects of lymphadenectomy performance in radical surgery based on structural variations of visceral vessels in 91 patients with stomach cancer. Preoperative helical computer tomography in regimen of angiography was carried out on 91 patients. Variant anatomy of visceral vessels was detected in 31 patients and that required change of surgical technique inorder to minimize intraoperative risks of great vessel damage and allowed performing lymphadenectomy successfully.